Synthesis and antioxidant activities of phenol derivatives from 1,6-bis (dimethoxyphenyl)hexane-1,6-dione - Artunc, Tekin; Menzek, Abdullah; Taslimi, Parham; Gülçin, İlhami; Kazaz, Cavit; Sahin, Ertan; Taslimi, Parham (Academic Press Inc Elsevier Science, 2020)
[Abstract not Available]
Keywords: Anhydrase Inhibitory Properties; In-Vitro Antioxidant; Carbonic-Anhydrase; Polyphenol Contents; Crystal-Structure; Cyclohexanonyl Bromophenol; Anticholinergic Activities; 1st Synthesis; Acetylcholinesterase; Butyrylcholinesterase